1977
DOI: 10.1159/000222005
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy Eradication Project of Malta

Abstract: This is the first publication of the initial 5-year-period of the eradication programme since its introduction in the Maltese Islands in the second half of 1972. All patients were treated with a combined drug regimen, its chief components being rifampicin (RMP), prothionamide (PTH), isoniazid (INH) and diaminodiphenyl-sulfone (DDS). To simplify the therapeutic technique, PTH, INH and DDS were given as a fixed combination. Other medications, such as DDS-free regimens, were whenever possible also given as fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Pearson and his colleagues in Malaysia found that the average incubation period for dapsone-resistant relapse, in LL and BL patients still receiving dapsone, was 15·8 (range 3-24) years after commencing sulphone therapy; 2 in Ethiopia it was 8·7 (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] years; 3 and rarely, it can take over 30 years. 4 Relapse rates and the timing of relapse after completing dapsone monotherapy vary somewhat, depending partly on the dose of dapsone given, and the duration and regularity of treatment.…”
mentioning
confidence: 99%
“…Pearson and his colleagues in Malaysia found that the average incubation period for dapsone-resistant relapse, in LL and BL patients still receiving dapsone, was 15·8 (range 3-24) years after commencing sulphone therapy; 2 in Ethiopia it was 8·7 (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] years; 3 and rarely, it can take over 30 years. 4 Relapse rates and the timing of relapse after completing dapsone monotherapy vary somewhat, depending partly on the dose of dapsone given, and the duration and regularity of treatment.…”
mentioning
confidence: 99%
“…The Seventh WHO Expert Committee on Leprosy, which met in Geneva from 26 May to 3 June 1997, considered the possibility of further shortening the duration of MDT. This possibility is being evaluated in an ongoing rifampicin-ofloxacin field trial, which is a multicentre, double-blind trial organized by the Steering Committee on Chemotherapy of Mycobacterial Diseases (THEMYC), a component of the UNDP/World Bank/WHO Special Programme for Research and Training in Tropical Diseases (TDR).…”
Section: " Further Shortening Duration Of Mb Leprosy Treatmentmentioning
confidence: 99%
“…Nonetheless, prothionamide was used in combination with rifampin, isoniazid, and dapsone in leprosy patients in Malta 15 and resulted in reliable cures, while being well tolerated. This experience in Malta provided the first suggestion that finite and not life-long therapy could result in a cure for all forms of leprosy.…”
Section: Introductionmentioning
confidence: 99%